1994
DOI: 10.1111/j.1365-2222.1994.tb00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational rhinoconjunctivitis and asthma caused by Tetranychus urticae (red spider mite). A case report

Abstract: This paper highlights a clinical case of a patient suffering bronchial asthma and rhinoconjunctivitis due to sensitization to Tetranychus urticae (TU), commonly known as the red spider mite, which belongs to the Prostigmata sub-order of the Tetranychidae family, in relation to a work environment (a carnation nursery). Both prick and intradermal skin tests were positive, as well as specific bronchial challenge tests with TU extract. Specific IgE was demonstrated by RAST (Class 3). Unspecific bronchial provocati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Among the mites present in horticultural environments, the following have clinical importance: phytophagus mites belonging to the family Tetranychidae [10][11][12][13][14][15][16][17][18][19][20] (genera Tetranychus and Panonychus) [21][22][23][24][25][26], and predator mites belonging to the families Phytoseiidae (genera Phytoseiulus and Amblyseius), Dermanyssidae (genus Hypoaspis) [27,28,29•], and Hemisarcoptidae (genus Hemisarcoptes) [30]. The main symptoms associated with sensitization and exposure to Tetranychidae mites (red spiders) are rhinoconjunctivitis and asthma.…”
Section: Mites Of Allergenic Importance In Agricultural and Occupatiomentioning
confidence: 99%
“…Among the mites present in horticultural environments, the following have clinical importance: phytophagus mites belonging to the family Tetranychidae [10][11][12][13][14][15][16][17][18][19][20] (genera Tetranychus and Panonychus) [21][22][23][24][25][26], and predator mites belonging to the families Phytoseiidae (genera Phytoseiulus and Amblyseius), Dermanyssidae (genus Hypoaspis) [27,28,29•], and Hemisarcoptidae (genus Hemisarcoptes) [30]. The main symptoms associated with sensitization and exposure to Tetranychidae mites (red spiders) are rhinoconjunctivitis and asthma.…”
Section: Mites Of Allergenic Importance In Agricultural and Occupatiomentioning
confidence: 99%
“…Other species of mites such as spider mites intervene in other professional environments [Panonychus ulmi in apple growers, Panonychus citri in citrus growers and Tetranychus urticae (345)(346)(347)(348)(349)(350) and Ornithonyssus sylviarum in poultry breeders (351)]. In Korea, the citrus red mite (P. citri) is also a common sensitizing allergen in children living in rural areas near citrus orchards (352,353).…”
Section: Other Mitesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] They are classified in the order Prostigmata, family Tetranichidae, subfamily Tetranichynae. The other spider mite, citrus red mite (Panonychus citri), is the most important inhalant allergen related to occupational asthma found in citrus farm farmers.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 All previous TSM-related reports have been confined to occupational exposures. [2][3][4][5][6][7][8] Although house-dust mite (HDM) has been known as the most important allergen in Korea, 11 a recent investigation demonstrated that TSM could be one of the prevalent inhalant allergens in nonfarmers as well as farmers in pear orchards. 12 Skin prick test (SPT) results of adult asthmatic patients complaining of summer-type asthma indicated that TSM was second in prevalence of sensitivity to HDM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation